Investigating whether socially acquired nocebo effects can spread to other treatments - Cosette Saunders; Winston Tan; Kirsten Barnes; Nicolas McNair; Ben Colagiuri (Scientific Reports)
Abstract Observation of another’s treatment side effects can elicit side effects in the observer, even when the treatment is a placebo. This study investigated whether these socially acquired side effects can generalise to similar treatments. Healthy volunteers (N = 120) participated in a study ostensibly comparing the effect of two cognitive enhancers (placebos). Participants were randomised to one of four experimental groups. The three treatment groups comprised: social modelling of side effects associated with the same treatment; social modelling of side effects associated with the different treatment; and a verbal suggestion only group (i.e., no social modelling). The fourth group was a no-treatment control group. The primary outcome was severity of side effects reported. Groups that received placebos reported increased symptom severity, i.e., showed a nocebo effect. Surprisingly, primary outcome analysis revealed no significant enhancement of the nocebo effect due to social modelling. However, there was an additive effect of social modelling on general side effects (planned secondary outcome) and specifically for headaches and dizziness (exploratory analysis), both of which generalised across treatments. Therefore, preliminary findings suggest that socially induced nocebo side effects may not always occur, but when they do, they can generalise beyond identical treatments. This warrants replication and raises significant concern given the widespread sharing of treatment-related information, potentially contributing to the societal burden of nocebo effects.